Limits on Fast Radio Bursts and other transient sources at 182 MHz using the Murchison Widefield Array - Rowlinson, A.; Bell, M.; Murphy, T.; Trott, C.; Hurley-Walker, N.; Johnston, S.; Tingay, Steven; Kaplan, D.; Carbone, D.; Hancock, P.; Feng, L.; Offringa, A.; et al. (Oxford University Press, 2016)
We present a survey for transient and variable sources, on time-scales from 28 s to ~1 yr, using the Murchison Widefield Array (MWA) at 182 MHz. Down to a detection threshold of 0.285 Jy, no transient candidates were identified, making this the most constraining low-frequency survey to date and placing a limit on the surface density of transients of <4.1 × 10-7 deg-2 for the shortest time-scale considered. At these frequencies, emission from Fast Radio Bursts (FRBs) is expected to be detectable in the shortest time-scale images without any corrections for interstellar or intergalactic dispersion. At an FRB limiting flux density of 7980 Jy, we find a rate of <82 FRBs per sky per day for dispersion measures <700 pc cm-3. Assuming a cosmological population of standard candles, our rate limits are consistent with the FRB rates obtained by Thornton et al. if they have a flat spectral slope. Finally, we conduct an initial variability survey of sources in the field with flux densities = 0.5 Jy and identify no sources with significant variability in their light curves. However, we note that substantial further work is required to fully characterize both the short-term and low-level variability within this field.